Connotative and Denotative Meaning in Fred Neil’s “Everybody’s Talkin” Song - Paisal Ramdani; R Myrna Nur Sakinah (English Language and Literature, 2023)
This study analyzes the myths in the lyrics of "Everybody's Talkin'" by Fred Neil. The researcher uses a qualitative descriptive method because the research results and the content of this study are in the form of words that must be explained. In reviewing the data, this study uses Roland Barthes' theory where the discussion focuses on denotation, connotation, and myth contained in the lyrics of the song Everyday's Talking by Fred Neil. This study provides new results regarding denotation and myths that develop about abstract life through the use of denotative, connotative, and mythical meanings formed from the relationship between the two meanings that question human life. One of the myths found in this research is the word sun, which in this study has a myth about the giver of light, warmth or the giver of life and happiness. The human problem in this case is the emptiness of feelings without happiness. The emptiness that is experienced in this lyric is about someone who has a desire to travel to find happiness because happiness is not found in the midst of the hustle and bustle of social life. Until the meaning of sun extends to abstract form of happiness.